Basic trends of psychological supports in the Great East Japan Earthquake - Ono, Haruka; Tsuchiya, Satomi; Ito, Daisuke; Takada, Kumiko; Sugiyama, Chikaze; Niikawa, Yoko; Ohtani, Tetsuhiro; Koseki, Shunsuke; Koseki, Mami (Journal of Health Psychology Research, 2020)
Psychological interventions conducted in relation to the Great East Japan Earthquake were categorized. We reviewed published research articles focusing on concerns over psychological support for the victims of the Great East Japan Earthquake by using CiNii and Google Scholar databases conducted in May 2017. The keywords for the searches included “Great East Japan Earthquake,” “group,” and “psychology.” As a result, 10 articles were extracted. The subjects, procedures, content of interventions, implementers, indicators, results of the research, and study tasks in the disaster area were identified. The results suggested that strategies necessary for assessing intervention subjects include setting the dependent and manipulated variables, and the establishment of operations to maintain the intervention.